Preparation method and application of manganese-based metal oxide nanoelectrocatalytic material

CN116695166BActive Publication Date: 2026-10-09JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310674581.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2026-10-09
Estimated Expiration
2043-06-08

AI Technical Summary

Technical Problem

[0006]然而,温度驱动的相变过程发生迅速且难以调控

Benefits of technology

(1)采用简单的水热、退火等方法实现锰基金属氧化物纳米电催化材料的制备,制备过程简单,可控性强,适合用于大规模工业生产;相比较于现有的锰基金属氧化物纳米电催化剂的制备方法,能够有效拓宽纳米材料的相变温度区间,抓取不完全相变的中间状态并构建异质界面,使得催化剂具备丰富的界面结构与独特的电子结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116695166B_ABST
    Figure CN116695166B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of nanometer materials, and provides a manganese-based metal oxide nanometer electrocatalytic material, which comprises a manganese-based metal oxide nanometer material and a substrate, the manganese-based metal oxide nanometer material comprises Mn, A and B, the A is one or more of alkali metals or alkaline earth metals, the B is one or more of other transition metal elements except Mn; the molar ratio of Mn, A and B is 0.6-1:0-0.4:0-0.4. The preparation of the manganese-based metal oxide nanometer electrocatalytic material is realized by simple hydrothermal and annealing methods, the preparation process is simple, controllable and suitable for large-scale industrial production; the phase transition temperature interval of the nanometer material is effectively widened, the intermediate state of incomplete phase transition is captured and a heterojunction is constructed, and a new method is provided for the development of future hydrogen energy and the expansion of application in the field of electrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials technology, and particularly relates to a method for preparing and applying manganese-based metal oxide nano-electrocatalytic materials. Background Technology

[0002] With the development of the Industrial Revolution and modern production technologies, the demand for natural gas, oil, and coal is increasing. However, the non-renewable nature of these energy sources will greatly hinder the development of modern production technologies and the economy and people's livelihoods. Therefore, it is crucial to find alternative clean and renewable energy sources.

[0003] Hydrogen energy, as a green and clean energy source, has high energy density, produces clean and green products, and is not limited by factors such as regional environment and regional reserve differences. It is considered one of the most promising renewable energy sources that can replace fossil fuels.

[0004] Electrocatalytic water splitting is an important method for hydrogen production; however, the oxygen evolution reaction at the anode is limited by thermodynamic constraints, hindering the rapid four-step electron transfer process and becoming a bottleneck in electrocatalytic hydrogen production technology. Currently, the most effective anode catalysts are oxides of precious metals such as iridium and ruthenium, but these are expensive and have low reserves. Therefore, research on catalysts based on transition metals such as iron, cobalt, nickel, and manganese has become mainstream. Manganese, a transition metal, is inexpensive and abundant, showing great application potential, making the development of manganese-based metal oxide nano-electrocatalytic materials imperative.

[0005] The establishment of heterogeneous interfaces and the synergistic effect between transition metal active sites are considered important factors in improving electrocatalytic performance. Constructing multiphase coexistence states, through close interactions between phases and abundant heterogeneous interface structures, can promote rapid mass transfer and charge transfer, achieving highly efficient catalytic reactions. Obtaining tightly composite nanomaterials through phase transition processes is a promising method for developing highly efficient electrocatalysts.

[0006] However, temperature-driven phase transitions occur rapidly and are difficult to control. Expanding the phase transition range through controllable means, obtaining multiphase composite nanomaterials during phase transitions, and applying them in the field of electrocatalysis remains a formidable challenge. Summary of the Invention

[0007] The purpose of this invention is to provide a method for preparing manganese-based metal oxide nano-electrocatalytic materials and their applications, aiming to solve the problems mentioned in the background art.

[0008] The present invention is implemented as follows: a method for preparing a manganese-based metal oxide nano-electrocatalytic material, wherein the manganese-based metal oxide nano-electrocatalytic material comprises a manganese-based metal oxide nanomaterial and a substrate, wherein the manganese-based metal oxide nanomaterial comprises Mn, A and B, wherein A is one or more of alkali metals or alkaline earth metals, and B is one or more of other transition metal elements other than Mn; the molar ratio of Mn, A and B is 0.6-1:0-0.4:0-0.4.

[0009] In a further technical solution, A is at least one of Ca, Sr, Ba, K, or Na; and B is at least one of Fe, Co, or Ni.

[0010] In a further technical solution, the substrate is at least one of a metal mesh or a fiber fabric.

[0011] A further technical solution, the preparation method includes the following steps: Step 1: Weigh out potassium permanganate, alkali metal salt / alkaline earth metal salt and transition metal salt according to the proportions, add them to ultrapure water and dissolve them to obtain the first solution; Step 2: Add excess ethyl acetate to the first solution obtained in Step 1 to obtain the second solution; Step 3: Transfer the second solution obtained in step 2 to a hydrothermal device at a certain temperature and add the substrate to react. Wash, centrifuge and dry to obtain metal ion-doped sodium manganese ore nanosheets. Step 4: Transfer the metal ion-doped sodium manganese ore nanosheets obtained in Step 3 into a muffle furnace and anneal them at a certain temperature to undergo phase transformation, thereby obtaining manganese-based metal oxide nano-electrocatalytic materials.

[0012] In a further technical solution, the alkali metal / alkaline earth metal salt in step 1 is selected from at least one of calcium chloride, strontium chloride, barium chloride, potassium chloride, and sodium chloride, and the transition metal salt is at least one of the acetate, nitrate, or sulfate of Ni, Co, or Fe.

[0013] In a further technical solution, in step 3, the hydrothermal reaction temperature is 60–100°C, and the hydrothermal reaction time is 3–15 h.

[0014] In a further technical solution, in step 4, an annealing phase transformation is carried out in an air atmosphere at 200–800°C, the annealing phase transformation time is 2–5 h, the heating rate is 5–10°C / min, and the mixture is naturally cooled to room temperature.

[0015] Another objective of this invention is to provide the application of a manganese-based metal oxide nano-electrocatalyst material prepared according to the above-described method for preparing manganese-based metal oxide nano-electrocatalyst materials in an electrochemical water splitting process for oxygen production.

[0016] The present invention provides a method for preparing manganese-based metal oxide nano-electrocatalyst materials and their applications, the beneficial effects of which are as follows: (1) Manganese-based metal oxide nano-electrocatalysts are prepared by simple hydrothermal and annealing methods. The preparation process is simple, highly controllable, and suitable for large-scale industrial production. Compared with existing methods for preparing manganese-based metal oxide nano-electrocatalysts, this method can effectively broaden the phase transition temperature range of nanomaterials, capture the intermediate state of incomplete phase transitions and construct heterogeneous interfaces, so that the catalyst has rich interface structures and unique electronic structures.

[0017] (2) The manganese-based metal oxide nano-electrocatalytic material provided by the present invention has a highly efficient ability to electrocatalyze the splitting of water and oxygen evolution, which can be compared with the best noble metal-based catalysts and nickel-iron bimetallic hydroxide catalysts currently available. Compared with manganese-based oxide catalysts prepared by other methods of the same type, its performance is greatly improved, and it also shows excellent stability, providing a new method for the future development of hydrogen energy and the expansion of applications in the field of electrocatalysis. Attached Figure Description

[0018] Figure 1 XRD pattern of sample 1# in the preparation method and application of a manganese-based metal oxide nano-electrocatalytic material provided in this embodiment of the invention; Figure 2 XRD pattern of sample 2# in a method for preparing manganese-based metal oxide nano-electrocatalyst material and its application provided in this embodiment of the invention; Figure 3 XRD pattern of sample 3# in a method for preparing manganese-based metal oxide nano-electrocatalytic material and its application provided in this embodiment of the invention; Figure 4 XRD pattern of sample 4# in the preparation method and application of a manganese-based metal oxide nano-electrocatalytic material provided in this embodiment of the invention; Figure 5 XRD pattern of sample 5# in a method for preparing manganese-based metal oxide nano-electrocatalyst material provided in this embodiment of the invention and its application; Figure 6 XRD pattern of sample 6# in a method for preparing manganese-based metal oxide nano-electrocatalyst material provided in an embodiment of the present invention and its application; Figure 7 The XRD pattern of sample 7# is shown in the preparation method and application of a manganese-based metal oxide nano-electrocatalytic material provided in this embodiment of the invention.

[0019] Figure 8Micro-area electron diffraction pattern of sample 2# in the preparation method and application of a manganese-based metal oxide nano-electrocatalytic material provided in this embodiment of the invention.

[0020] Figure 9 The preparation method of manganese-based metal oxide nano-electrocatalytic material provided in the embodiments of the present invention and the performance of samples 1#, 2#, 3#, 4#, 5#, 6# and 7# in electrocatalytic water cracking oxygen desorption are shown in the figure.

[0021] Figure 10 The stability diagram of oxygen desorption by electrocatalytic water cracking of sample 2# is provided in the preparation method of manganese-based metal oxide nano-electrocatalytic material and its application in the embodiment of the present invention. Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0023] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.

[0024] An embodiment of the present invention provides a method for preparing a manganese-based metal oxide nano-electrocatalytic material, wherein the manganese-based metal oxide nano-electrocatalytic material comprises a manganese-based metal oxide nanomaterial and a substrate, wherein the manganese-based metal oxide nanomaterial comprises Mn, A and B, wherein A is one or more of alkali metals or alkaline earth metals, and B is one or more of other transition metal elements other than Mn; the molar ratio of Mn, A and B is 0.6-1:0-0.4:0-0.4.

[0025] In this embodiment of the invention, A is at least one of Ca, Sr, Ba, K or Na; and B is at least one of Fe, Co or Ni.

[0026] The substrate is at least one of a metal mesh or a fiber fabric; further, the substrate is selected from at least one of a nickel mesh or a carbon cloth.

[0027] In a preferred embodiment of the present invention, the preparation method includes the following steps: Step 1: Weigh out potassium permanganate, alkali metal salt / alkaline earth metal salt, and transition metal salt according to the proportions, add them to ultrapure water and dissolve them to obtain the first solution; Step 2: Add excess ethyl acetate to the first solution obtained in Step 1 to obtain the second solution; Step 3: Transfer the second solution obtained in step 2 to a hydrothermal device at a certain temperature and add the substrate to react. Wash, centrifuge and dry to obtain metal ion-doped sodium manganese ore nanosheets. Step 4: Transfer the metal ion-doped sodium manganese ore nanosheets obtained in Step 3 into a muffle furnace and anneal them at a certain temperature to undergo phase transformation, thereby obtaining manganese-based metal oxide nano-electrocatalytic materials.

[0028] In this embodiment of the invention, a simple combination of hydrothermal and annealing methods is employed to broaden the phase transition temperature range of nanomaterials, capture the intermediate state of incomplete phase transitions, and construct a composite heterogeneous interface. The manganese-based metal oxide nano-electrocatalytic material of this invention possesses rich interfacial structures and unique electronic structures, exhibiting exceptionally excellent performance in water electrolysis for oxygen production. It also demonstrates good stability, and its preparation method is simple and reproducible, solving the problem of insufficient utilization of the phase transition process in inorganic solid materials due to a narrow phase transition temperature range and rapid phase transition. Applying the aforementioned manganese-based metal oxide nano-electrocatalytic material to the electrochemical water splitting oxygen production process offers strong controllability, low cost, and suitability for large-scale industrial production.

[0029] In a preferred embodiment of the present invention, the alkali metal / alkaline earth metal salt in step 1 is selected from at least one of calcium chloride, strontium chloride, barium chloride, potassium chloride, and sodium chloride, and the transition metal salt is at least one of the acetate, nitrate, or sulfate of Ni, Co, or Fe.

[0030] In a preferred embodiment of the present invention, in step 3, the hydrothermal reaction temperature is 60-100°C and the hydrothermal reaction time is 3-15 hours.

[0031] In a preferred embodiment of the present invention, in step 4, an annealing phase transformation is performed in an air atmosphere at 200–800°C for 2–5 hours, with a heating rate of 5–10°C / min, followed by natural cooling to room temperature.

[0032] As a preferred embodiment of the present invention, a variety of samples were prepared, specifically: Sample 1# was prepared: Potassium permanganate, nickel acetate tetrahydrate, and calcium chloride dihydrate in a mass ratio of 5:4:2 were added sequentially to ultrapure water, stirred and dissolved, and then transferred to a flask. Excess ethyl acetate was added, and a nickel mesh was added as a substrate. The mixture was hydrothermally reacted at 80°C for 10 hours, and then centrifuged and dried to obtain the nickel-doped calcium-sodium manganese ore, namely Ca,Ni-(Ni)MnO2.

[0033] Sample 2# was prepared: (1) Potassium permanganate, nickel acetate tetrahydrate and calcium chloride dihydrate in a mass ratio of 5:4:2 were added to ultrapure water in sequence. After stirring and dissolving, the mixture was transferred to a flask, excess ethyl acetate was added, and nickel mesh was added as a substrate. The mixture was hydrothermally reacted at 80°C for 10 hours, and then centrifuged and dried to obtain nickel-doped calcium-sodium manganese ore.

[0034] (2) The nickel-doped calcium-sodium manganese ore obtained in step (1) is transferred into a muffle furnace for annealing treatment, calcined at 500°C for 3 hours in air atmosphere, and naturally cooled to room temperature to obtain the nickel-doped calcium-sodium manganese ore / nickel manganate composite nanomaterial, namely Ca,Ni-(Ni)MnO2 / NiMnO3.

[0035] Sample 3# was prepared: Compared with Sample 2#, except that the annealing temperature in the preparation of the nano-electrocatalyst was 400℃, the preparation process was the same as that of Sample 2#.

[0036] Sample 4# was prepared: Compared with Sample 2#, except that the annealing temperature in the preparation of the nano-electrocatalyst was 600℃, the preparation process was the same as that of Sample 2#.

[0037] Sample 5# was prepared: Potassium permanganate and nickel acetate tetrahydrate in a mass ratio of 5:4 were sequentially added to ultrapure water, stirred until dissolved, and then transferred to a flask. Excess ethyl acetate was added, and a nickel mesh was added as a substrate. The mixture was hydrothermally reacted at 80°C for 10 hours, followed by centrifugation and drying to obtain the nickel-doped sodium manganese ore, i.e., Ni. x Mn 1-x O2 Sample 6# was prepared: (1) Potassium permanganate and nickel acetate tetrahydrate in a mass ratio of 5:4 were added to ultrapure water in sequence, stirred and dissolved, and then transferred to a flask. Excess ethyl acetate was added, and nickel mesh was added as a base. The mixture was hydrothermally reacted at 80°C for 10 hours, and then centrifuged and dried to obtain nickel-doped sodium manganese ore.

[0038] (2) Take the calcium-water sodium manganese ore obtained in step (1) and transfer it into a muffle furnace for annealing. Calcine it at 450°C for 3 hours in an air atmosphere and cool it naturally to room temperature to obtain the nickel manganate nanomaterial, i.e., NiMnO3.

[0039] Sample 7# was prepared: Compared with sample 6#, except that the annealing temperature in the preparation of the nano-electrocatalyst was 400℃, the preparation process was the same as that of sample 6#.

[0040] X-ray diffraction (XRD) analysis was performed on samples 1#, 2#, 3#, 4#, 5#, 6#, and 7#. Specific results are as follows: Figure 1-7As shown. The XRD patterns of prepared samples 1# and 5# correspond to the typical structural characteristics of naphthoic ore, indicating that the introduction of Ca does not change the phase structure of naphthoic ore. The XRD patterns of prepared samples 3# and 7# show no significant changes compared to samples 1# and 5#, and the characteristic diffraction peaks of naphthoic ore are retained, indicating that naphthoic ore has not undergone phase transformation at 400℃. The XRD pattern of prepared sample 2# shows diffraction peaks corresponding to those in standard card PDF#75-2089, indicating that naphthoic ore treated at 500℃ undergoes partial phase transformation to NiMnO3 when doped with Ca. The XRD pattern of prepared sample 4# shows diffraction peaks consistent with those in standard cards PDF#75-2089 and PDF#88-0241, indicating that naphthoic ore treated at 600℃ undergoes complete phase transformation to NiMnO3 and NiMn2O4 when doped with Ca. The XRD pattern of sample 6# showed diffraction peaks completely consistent with the standard card PDF#75-2089, indicating that without Ca doping, naphthalene hydrate completely transformed into NiMnO3 at 450℃. This demonstrates that the introduction of Ca altered the temperature range at which the naphthalene hydrate underwent a phase transition.

[0041] In addition, micro-area electron diffraction tests were performed on the prepared sample 2#, and the specific results are as follows: Figure 8 As shown, it is demonstrated that sodium manganese ore and nickel manganate coexist in sample 2#. After Ca is introduced into nickel-doped sodium manganese ore, the phase transition temperature range is extended, and the phase transition is not complete even at 500℃.

[0042] Simultaneously, electrocatalytic performance tests were conducted. Specifically, the electrocatalytic cracking of water and oxygen evolution reaction using manganese-based metal oxide nanomaterials was performed, including the following steps: (1) The electrocatalytic water splitting reaction for oxygen production was carried out in an electrolytic cell and tested using a Shanghai Chenhua CHI760e electrochemical workstation with a three-electrode system. The electrolyte was 1M KOH solution. Before the formal test, the 1M KOH solution needed to be saturated with oxygen for at least 30 minutes.

[0043] (2) Three-electrode system: Samples 1#, 2#, 3#, 4#, 5#, 6#, and 7# were used as working electrodes, HgO electrode as reference electrode, and carbon rod as counter electrode. All test voltages were calculated according to formula E. RHE =E+0.059*pH+0.098 is converted to the standard hydrogen electrode potential.

[0044] (3) Samples 1#, 2#, 3#, 4#, 5#, 6# and 7# were activated using cyclic voltammetry, with a test potential range of 0.1 to 0.9 V and a scan rate of 20 mV s. -1 Scan 100 times.

[0045] (4) Electrocatalytic water splitting and oxygen evolution reaction were performed on test samples 1#, 2#, 3#, 4#, 5#, 6# and 7# using linear sweep voltammetry. The test potential range was 0.1 to 0.9 V, and the scan rate was 5 mV s. -1 Performance graph as shown Figure 9 As shown. This illustrates that the prepared sample 2#, a nickel-doped calcium-sodium manganese ore / nickel manganate composite nanomaterial, namely Ca,Ni-(Ni)MnO2 / NiMnO3, exhibits the best electrocatalytic performance, far exceeding that of the samples prepared in other examples.

[0046] Electrocatalytic stability tests were also conducted. Specifically, the electrocatalytic cracking of water and oxygen evolution reaction using manganese-based metal oxide nanomaterials included the following steps: (1) The electrocatalytic water splitting reaction for oxygen production was carried out in an electrolytic cell and tested using a Shanghai Chenhua CHI760e electrochemical workstation with a three-electrode system. The electrolyte was 1M KOH solution. Before the formal test, the 1M KOH solution needed to be saturated with oxygen for at least 30 minutes.

[0047] (2) Three-electrode system: The prepared sample 2# is used as the working electrode, the HgO electrode is used as the reference electrode, and the carbon rod is used as the counter electrode.

[0048] (3) The stability of the sample 2# was tested using the chronoamperometry method, with a test current density of 500 mA cm⁻¹. -2 The test lasted for 500 hours, and the test results are as follows: Figure 10 As shown, sample 2# exhibited good electrocatalytic stability.

[0049] Therefore, the prepared sample #2, the nickel-doped calcium-sodium manganese hydrate / nickel manganate composite nanomaterial, namely Ca,Ni-(Ni)MnO2 / NiMnO, exhibits excellent electrocatalytic oxygen evolution reaction (OER) performance in water splitting. The phase transition temperature range of inorganic nanomaterials, the capture of intermediate states during incomplete phase transitions, and the construction of composite heterogeneous interfaces are achieved through simple hydrothermal and annealing methods. The entire process is highly controllable and suitable for large-scale industrial production, largely solving the problem of the thermodynamic limitation hindering the rapid four-step electron transfer in the anodic OER half-reaction of electrocatalytic water splitting. Furthermore, the provided preparation method is simple and offers valuable insights for broadening the phase transition temperature range of other oxides and synthesizing novel catalytic materials.

[0050] It should be noted that the method for preparing manganese-based metal oxide nanomaterials provided by the present invention is used for electrocatalytic cracking of water oxygen evolution reaction. By capturing the multiphase coexistence complex state during the phase transition process, rich heterogeneous interfaces are constructed between the phases, making electron transfer more rapid and accelerating the reaction kinetics process, thereby improving the catalytic performance of the material.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a manganese-based metal oxide nano-electrocatalytic material, characterized in that, Includes the following steps: Step 1: Weigh out potassium permanganate, nickel acetate tetrahydrate and calcium chloride dihydrate according to the proportions and dissolve them in ultrapure water to obtain the first solution; Step 2: Add excess ethyl acetate to the first solution obtained in Step 1 to obtain the second solution; Step 3: Transfer the second solution obtained in Step 2 to a hydrothermal device and add the substrate to react. Wash, centrifuge and dry to obtain nickel-doped calcium-water sodium manganese ore. Step 4: Transfer the nickel-doped calcium-sodium manganese ore obtained in Step 3 into a muffle furnace and anneal it at 500°C for 3 hours in air atmosphere to obtain nickel-doped calcium-sodium manganese ore / nickel manganate composite nano-electrocatalytic material.

2. The method for preparing manganese-based metal oxide nano-electrocatalytic materials according to claim 1, characterized in that, The substrate is at least one of a metal mesh or a fiber fabric.

3. The method for preparing manganese-based metal oxide nano-electrocatalytic materials according to claim 1, characterized in that, In step 3, the hydrothermal reaction temperature is 60–100°C, and the hydrothermal reaction time is 3–15 h.

4. The method for preparing manganese-based metal oxide nano-electrocatalytic materials according to claim 1, characterized in that, In step 1, the mass ratio of potassium permanganate, nickel acetate tetrahydrate, and calcium chloride dihydrate is 5:4:

2.

5. The application of a nickel-doped calcium-sodium manganese ore / nickel manganate composite nano-electrocatalytic material prepared by the method according to any one of claims 1-4 in an electrochemical water splitting process for oxygen production.

Citation Information

Patent Citations

  • Spray Pyrolysis Synthesis of Mesoporous Positive Electrode Materials for High Energy Lithium-Ion Batteries

    US20120282522A1

  • Compositions and methods for enhancing electrocatalytic efficiencies

    US20210198792A1